Successful Treatment of Recurrent Primary Sclerosing Cholangitis after Orthotopic Liver Transplantation with Oral Vancomycin - Yinka K. Davies; Cynthia J. Tsay; Dario V. Caccamo; Kathleen M. Cox; Ricardo O. Castillo; Kenneth L. Cox (Case Reports in Transplantation, 2013)
Primary sclerosing cholangitis (PSC) is a progressive, cholestatic disease of the liver that is marked by inflammation of the bile ducts and damage to the hepatic biliary tree. Approximately 60–70% of patients also have inflammatory bowel disease and progression of PSC can lead to ulcerative colitis and cirrhosis of the liver. Due to limited understanding of the etiology and mechanism of PSC, the only existing treatment option is orthotopic liver transplantation (OLT); however, recurrence of PSC, after OLT is estimated to be between 5% and 35%. We discuss the successful treatment of a pediatric patient, with recurrent PSC, after OLT with oral Vancomycin.